Examination of the Reflections of the News on Democracy in the Local Press (1946-1960 Case of Malatya) - Doğan, İbrahim Halil; Aydın, Mesut (Fırat Üniversitesi, 2023)
Newspapers that we can express as the diaries of a nation; It contains information about the social and political texture, values, personalities and institutions of the period in which it was published. Newspapers are not only the news source of the period in which they were published, but also provide a rich data source that can be used by many disciplines from politics to history, from economy to education, from law to sociology. In the research, it is aimed to examine the reflections of the news about democracy between 1946-1960 in the local press of Malatya. The research has a qualitative method and a case study model was used. The newspapers Fırat, Malatya Postası and Yeni Malatya Postası, which were included in the Malatya local press between 1946 and 1960 in the National Library Periodicals Archive, were determined as the study group of the research. Among the determined newspapers, nearly 7000 newspaper pages were scanned and democracy news was taken as a basis and criterion sampling method was used. As a result of the scanning, a total of 891 news related to the subject of democracy were reached, classified in eight categories and coded. The document analysis method was used as a data collection tool in the research, and the content analysis technique was used in the analysis of the data. In line with the analysis, it was concluded that the understanding of democracy, culture, institutions, political texture and personalities of the period from the transition of Turkey to the multi-party political life in 1946 until 1960 were tried to be reflected through the example of the Malatya local press.

Bir milletin günlükleri olarak ifade edebileceğimiz gazeteler; çıkarıldığı dönemin toplumsal ve siyasal dokusu, değerleri, kişilikleri ve kurumları hakkında bilgiler içermektedir. Gazeteler, yalnızca yayımlandığı dönemin haber kaynağı değil, sonraki yıllarda da siyasetten tarihe, ekonomiden eğitime, hukuktan sosyolojiye birçok bilim dalının kullanabileceği zengin bir veri kaynağı sunmaktadır. Araştırmada, 1946-1960 yılları arasındaki demokrasi konulu haberlerin Malatya yerel basınındaki yansımalarını incelemek amaçlanmıştır. Araştırma, nitel bir yönteme sahip olup durum çalışması modeli kullanılmıştır. Milli Kütüphane Süreli Yayınlar Arşivindeki 1946-1960 yılları arasında Malatya yerel basınında yer alan Fırat, Malatya Postası ve Yeni Malatya Postası gazeteleri araştırmanın çalışma grubu olarak belirlenmiştir. Belirlenen gazeteler içerisinden 7000’ne yakın gazete sayfası taranıp demokrasi haberleri esas alınmış ve ölçüt örnekleme yöntemi kullanılmıştır. Tarama sonucunda demokrasi konusuyla ilişkili toplam 891 habere ulaşılmış, sekiz kategoride tasnif edilerek kodlamalar yapılmıştır. Araştırmada veri toplama aracı olarak doküman incelemesi yöntemi kullanılmış, verilerin analizinde ise içerik analizi tekniği uygulanmıştır. Yapılan analizler doğrultusunda, 1946’da Türkiye’nin çok partili siyasal hayata geçişinden 1960’a kadarki süreçte demokrasi anlayışı, kültürü, kurumları, dönemin siyasi dokusu ve kişilikleri Malatya yerel basını örneği üzerinden yansıtılmaya çalışıldığı sonucuna ulaşılmıştır.
DEMOKRASİ KONULU HABERLERİN YEREL BASINDAKİ YANSIMALARININ İNCELENMESİ (1946-1960 MALATYA ÖRNEĞİ)